2017
DOI: 10.1002/bmc.3945
|View full text |Cite
|
Sign up to set email alerts
|

Application of capillary electrophoresis with capacitively coupled contactless conductivity detection (CE‐C4D): An update

Abstract: Capacitively coupled contactless conductivity detection (C D) has appeared as a powerful technique for the detection of compounds lacking chromogenic or fluorogenic group. Since our last review (Biomedical Chromatography 2014; 28: 1502-1506) several new capillary electrophoresis (CE)-C D methods have been reported. This review provides an update of the most recent utilization of CE-C D in the field of pharmaceutical, biomedical and food analysis covering the period from February 2014 to October 2016. The use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 80 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…In addition, advances in electrochemical detectors, such as CE-contactless coupled detection (CE-CCD) and CE-capacitively coupled contactless conductivity detection (CE-C 4 D), offered very sensitive methods [22,23]. Furthermore, the development of miniaturized CE systems (microchip-CE devices) allowed the monitoring of food analytes with rapidity and sensitivity, and their use was particularly important in the detection of frauds or contaminations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, advances in electrochemical detectors, such as CE-contactless coupled detection (CE-CCD) and CE-capacitively coupled contactless conductivity detection (CE-C 4 D), offered very sensitive methods [22,23]. Furthermore, the development of miniaturized CE systems (microchip-CE devices) allowed the monitoring of food analytes with rapidity and sensitivity, and their use was particularly important in the detection of frauds or contaminations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the applicability of the proposed approach, plasma samples from patients under treatment with TPM were analyzed according to the procedure described. It is important to mention that while the combination of CE‐C 4 D has been previously used for the analysis of small molecules including pharmaceutical compounds such as sildenafil/vardenafil , caffeine/paracetamol/ibuprofen , or antibiotics the application to serum samples is rarely reported. Figure shows the results obtained from 10 patients under treatment with TPM.…”
Section: Resultsmentioning
confidence: 99%
“…Elbashir et al. reviewed the applications of CE‐axial C 4 D to analyses in the pharmaceutical and biological fields and concluded that this approach was showing great promise. Wang et al.…”
Section: Applications In Different Clinical Fieldsmentioning
confidence: 99%